2010
DOI: 10.1159/000313370
|View full text |Cite
|
Sign up to set email alerts
|

Episodes of Overtreatment during the First Six Months in Children with Congenital Hypothyroidism and Their Relationships with Sustained Attention and Inhibitory Control at School Age

Abstract: Background/Aims: Contradictory results regarding the optimal initial dose of levothyroxine in children with congenital hypothyroidism (CH) hamper the clinical management of these children during their early infancy. We explore the relationships between the initial dose of levothyroxine and endocrine control during the first 6 months and cognition at school age. Subjects and Methods: Fifty children with CH, 14 boys (10 ± 3.1 years) and 36 girls (9.7 ± 2.6 years), at the Pediatric Endocrine Unit of the Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 79 publications
(34 reference statements)
3
22
0
4
Order By: Relevance
“…Such an association is also consistent with experimental studies showing the effects of chronic hypothyroidism on development (31). Overtreatment should also be avoided (32,33). These results highlight the need for careful monitoring of treatment adequacy throughout childhood and adulthood.…”
Section: Cognition Behavior and Socioeducational Attainmentsupporting
confidence: 86%
“…Such an association is also consistent with experimental studies showing the effects of chronic hypothyroidism on development (31). Overtreatment should also be avoided (32,33). These results highlight the need for careful monitoring of treatment adequacy throughout childhood and adulthood.…”
Section: Cognition Behavior and Socioeducational Attainmentsupporting
confidence: 86%
“…If the absence of over- and undertreatment would be a causative factor, a substantial proportion of all healthy newborns with normal thyroid function without over- or undertreatment in these periods would show ADHD-like or ASD-like behaviour, which is obviously not the case. Furthermore, the conclusion that overtreatment in the period 1–3 months is a causative factor for high ADA scores, and that the absence of overtreatment in the period 3–6 months is not, is in line with previous studies [3, 6]. One of these [6] suggests that at least a considerable proportion of the “difficult” patients experienced overtreatment in the period 1–3 months, because at 3 years they showed more advanced motor development than did the “easy” patients.…”
Section: Discussionsupporting
confidence: 91%
“…Thyroid abnormalities have been associated with attention deficit hyperactivity disorder (ADHD) in various studies [1-3]. This association is most clearly seen in a study on thyroid hormone resistance [1], where the majority of the patients were found to have ADHD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are no studies to show that treating these children with levothyroxine improves outcome, treatment for subclinical hypothyroidism is frequently recommended for the vulnerable first 2 or 3 years of life when brain development is thyroid hormone dependent [3]. It has also been suggested that overtreatment with levothyroxine in this time period may adversely affect neurodevelopmental outcomes and should be avoided [9, 10]. …”
Section: Introductionmentioning
confidence: 99%